Mental health model of acculturation among international students in Pakistan - Riaz, Muhammad Akram; Rafique, Rafiq; Riaz, Muhammad Naveed (Journal of International Students, 2025)
Many universities in Pakistan accept a substantial number of international students. International students who choose to study abroad face a variety of difficulties, including issues with acculturation, acculturative stress, and related mental health issues. This study examines the mental health model of acculturation among international students in Pakistan. The sample consisted of 450 international students. Data were collected from international students studying at Pakistani universities. The findings revealed that acculturation can lead to acculturative stress, and international students with a better social support network experience better psychological and sociocultural adaptation, which directly or indirectly impacts their psychological and social well-being. Moreover, some personal, social, and economic factors also affect the process of acculturation and mental health outcomes. The study's findings confirmed that acculturation is a process and can be tested as a mental health model.